Scaling-out gender transformative approaches in agriculture research for development - Hillenbrand, Emily; Obi, Chinedu; McDougall, Cynthia; Rossignoli, Cristiano (Taylor & Francis, 2024)
This paper looks at the spread and socialization of gender transformative approaches (GTA) within a network of research and development organizations that focus on gender and agriculture. We conducted in-depth interviews with 20 respondents from 19 development and research organizations who work in the agriculture sector and have some interest or engagement with GTA, and we analyzed the scaling drivers and patterns within and beyond this immediate network. The findings show a rapidly growing interest in GTA across the ecosystem, especially among organizations with a strong commitment to helping achieve gender equality. GTA are scaling out across the ecosystem in a nonlinear way, through both direct and indirect strategies. Factors such as the mandate and agency of an organization, as well as the persistence and passion of individual stakeholders appear to be important drivers in influencing how GTA are spreading. Despite the enthusiasm and high momentum for doing gender transformative work across the organizations, this study also surfaces serious reservations about how rapidly the terminology and/or tools related with GTA are being adopted, while there remain widely varying levels of understanding, gender expertise, and funding for the type of intensive effort that is required to achieve a true paradigm shift in the sector.